Library Service Satisfaction of library users in Cendrawasih University Library Unit - Thereseta Evilianingsih (Journal of Education and Vocational Research, 2016)
This study aims to identify and analyze how much influence the quality of library services to the satisfaction of the library users at the University Library of Cenderawasih. Research method used in this study is the method of observation, interviews, questionnaires, and literature study using a Likert scale and sampling method used is Probability Sampling with Proportional stratified random sampling, which means sampling of members of the population at random and stratified proportional so that samples obtained 90 samples. The analytical method used is multiple linear regression method. The results showed that the quality of service which consists of tangible, reliability, responsiveness, assurance, empathy, and together have a positive influence. Service quality has a significant effect on satisfaction library users at the University Library of Cenderawasih. The variables that have a significant influence on satisfaction library users are tangibles, reliability and empathy. Responsiveness and assurance does not have a significant influence on satisfaction in the Library Unit Uncen library users. The most dominant variable is empathy.